MODEL OF INCREASING THE COMPETITIVENESS OF MSMES: A COMMUNITY EDUCATION-BASED EMPOWERMENT PROCESS FOR MSME ACTORS IN REMPANGA VILLAGE - Saputra, Ramadhan Dian; Lukman, A. Ismail; Mustangin, Mustangin; Alisalman, Muhamad (Universitas Galuh, 2024)
Community empowerment is an effort to increase the capacity of the community so that they can overcome existing problems independently. Community empowerment is an effort to increase community capacity in dealing with problems that can hinder the community itself. This study aims to analyze the empowerment of MSME actors in Rempanga Village. The implementation of empowerment This selection method or technique will certainly have an impact on the success of the process and the results of empowerment activities. This study uses a qualitative approach because it is in accordance with the research objectives and the method used is a descriptive research method. The data collection techniques used are interview techniques, observation techniques, and document study techniques. Data analysis uses data reduction, data presentation, and conclusion drawn. Checking the validity of the data using triangulation techniques and sources. The results of the study show that the empowerment model is implemented through several stages of community empowerment which begins with the initial introduction phase of the MSME actor program to the program to be implemented. The second phase is carried out to identify community needs, and the third phase is community capacity building and the fourth phase is community independence.